Deceivers - Haddix, Margaret Peterson (New York Katherine Tegen Books, an imprint of HarperCollinsPublishers, 2020)
Told from separate viewpoints, as Finn, Emma, and Chess Greystone and Natalie Mayhew, ages eight to thirteen, continue their quest to rescue their mothers they must return to the alternate dimension where truth is illegal.
Ages 8-12.
Grades 4-6.
Accelerated Reader AR
Lexile
112897
Keywords: Missing persons -- Juvenile fiction; Siblings -- Juvenile fiction; Families -- Juvenile fiction; Honesty -- Juvenile fiction; Paranormal fiction; Family life -- Fiction; Supernatural -- Fiction; Juvenile Fiction -- Fantasy & Magic; Juvenile Fiction -- Family -- Siblings; Occult fiction; Children's stories; Fantasy fiction; Juvenile works; Paranormal fiction